2021
DOI: 10.1177/09603271211036122
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Neuroprotection of chromobox 7 knockout in the mouse after cerebral ischemia-reperfusion injury via nuclear factor E2-related factor 2/hemeoxygenase-1 signaling pathway

Abstract: Objective To explore the mechanism of chromobox 7 (CBX7)-mediated nuclear factor E2-related factor 2 (Nrf2)/hemeoxygenase-1 (HO-1) signaling pathway in the cerebral ischemia/reperfusion (I/R) injury. Methods The experimental wild-type (WT) and CBX7-/- mice were used to establish cerebral I/R models using the middle cerebral artery occlusion (MCAO) surgery to determine CBX7 levels at different time points after MCAO injury. For all mice, neurological behavior, infarct size, water content, and oxidative stress–r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It plays a part in chromatin remodeling and histone modification. Suppression of CBX7 expression has revealed protective effects against ischemia–reperfusion injury in the kidney ( Zhang et al, 2020 ) and brain ( Zhang et al, 2021b ) via different pathways. We showed that CBX7 expression was downregulated in AD patients, suggesting that this is a compensatory response in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a part in chromatin remodeling and histone modification. Suppression of CBX7 expression has revealed protective effects against ischemia–reperfusion injury in the kidney ( Zhang et al, 2020 ) and brain ( Zhang et al, 2021b ) via different pathways. We showed that CBX7 expression was downregulated in AD patients, suggesting that this is a compensatory response in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%